Editorial: trends and advanced materials for pavement and road infrastructure - Putra Jaya, Ramadhansyah; Norhidayah, Abdul Hassan; Erdem, Savas (Frontiers Media S.A., 2021)
A year with the Covid-19 pandemic has caused great impacts on all aspects of society worldwide. With the current challenges, this special issue offers four interesting technical papers comprising research on bitumen modification, pavement noise, waste material, and modeling of concrete bridges.